Exploring Work Climate among University Personnel - Lycel Lagnason Pacheco (PT FORMOSA CENDEKIA GLOBAL, 2023)
This was a descriptive study which used a survey questionnaire that determined the profile and characteristics of the complete enumeration of the teaching and non-teaching personnel in the areas of caring, cohesiveness, respect, trust, career and social growth and opportunity for input. The data were analyzed using descriptive and inferential statistics. Also, the mean which is a measure of central tendency was used to determine the work climate at Central Philippines State University. The most number of respondents were those from 31 to 45 years old, the females outnumbered males, majority were College Level/Graduate and most respondents were in the service for 10 years and below. The younger the personnel, the more that they were favorable with the work climate. Males were less favorable compared to the females. The college level/graduate personnel of the University found its work climate a more positive one compared to personnel with master’s and doctor’s degree. The work climate in the University was more positive for the permanent staff or non-teaching personnel and job order employees. The work climate at Central Philippines State University as to caring, cohesiveness, career and social growth and opportunity for input got an interpretation of highly favorable while it got moderately favorable as to respect and trust. There was a significant difference in the characteristics of CPSU teaching and non-teaching personnel in the areas of caring, respect, social growth and opportunity for input. There existed significant difference on the work climate among University personnel when grouped according to the respondents’ profile.